2021
DOI: 10.9787/kjbs.2021.53.4.411
|View full text |Cite
|
Sign up to set email alerts
|

Yearly Variation of Isoflavone Composition and Yield-Related Traits of 35 Korean Soybean Germplasm

Abstract: In this study, composition and agronomic traits, including yield-related traits, were investigated and compared among 35 Korean landrace germplasm for two years (2019 and 2020). The contents of 12 isoflavones were measured using high-performance liquid chromatography, and agronomic trait data were collected according to the Rural Development Administration criteria. Comparing isoflavone composition between the two years, all isoflavones, except glycitein, were generally higher in 2019. The values of yield-rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…We detected weaker positive correlations between total isoflavones and aglycones [DZE, GLE, and GNE (r = 0.46-0.82 in 2020 and r = 0.12-0.20 in 2021)]; and between total isoflavones and acetyl glucosides [ADZI and AGNI (r = 0.26-0.96 in 2020 and r = 0.47-0.95 in 2021)]. Across both years, DZI (r = 0.93 * * * , r = 0.89 * * * ), GNI (r = 0.94 * * * , r = 0.89 * * * ), MDZI (r = 0.94 * * * , r = 0.94 * * * ), MGNI (r = 0.94 * * * , r = 0.96 * * * ) and ADZI (r = 0.95 * * * , r = 0.96 * * * ) showed significantly strong positive correlations with TI and with each other, consistent with the results of other studies (Azam et al, 2020;Yoon et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…We detected weaker positive correlations between total isoflavones and aglycones [DZE, GLE, and GNE (r = 0.46-0.82 in 2020 and r = 0.12-0.20 in 2021)]; and between total isoflavones and acetyl glucosides [ADZI and AGNI (r = 0.26-0.96 in 2020 and r = 0.47-0.95 in 2021)]. Across both years, DZI (r = 0.93 * * * , r = 0.89 * * * ), GNI (r = 0.94 * * * , r = 0.89 * * * ), MDZI (r = 0.94 * * * , r = 0.94 * * * ), MGNI (r = 0.94 * * * , r = 0.96 * * * ) and ADZI (r = 0.95 * * * , r = 0.96 * * * ) showed significantly strong positive correlations with TI and with each other, consistent with the results of other studies (Azam et al, 2020;Yoon et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…Some studies have reported that the anthocyanin-based component of the seed coat color contributes to increasing the antioxidant activity of the soybeans and that the antioxidant activity decreases as the color of the seed coat of soybeans becomes lighter [ 43 , 44 ]. The samples that maintained the highest activity in both the first and second years were B17, B15, and B23 in the black group, revealing that the traits remained stable in these samples despite climatic variations [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The sum of the duration of daylight from June to September was 620.7 h in the normal year, whereas it amounted to 672.5 h in 2019, which was 51.8 h longer than in the normal year. The sum was 585.3 h in 2020, which was 35.4 h shorter than the normal year [ 22 ]. The decrease in the duration of daylight would have had the same effect as the shade stress, resulting in increased antioxidant components and efficacy due to the increase in anthocyanins.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations